Pengaruh Risiko Bisnis Dan Struktur Aktiva Terhadap Struktur Modal Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2020 - Resti Anggraini; Wahyu Indah Mursalini; Esi Sriyanti (Transformasi: Journal of Economics and Business Management, 2023)
This research aims to analyze the effect of Business Risk and Asset Structure on the Capital Structure of Manufacturing Companies in the Basic and Chemical Industry Sector listed on the Indonesia Stock Exchange. The sample in this study were 35 basic and chemical industry sector companies listed on the Indonesia Stock Exchange using the Purposive Sampling method for the 2018-2020 period. Based on multiple linear regression analysis, the variables of Business Risk and Asset Structure have an effect on Capital Structure with the equation Y = 2,968 – 7,865X1 – 2,355X2 + e. From the t-test, it was found that the variable X1 Business Risk had a significant effect on the Capital Structure with t count value is [-7,171] > t table [1,983] and sig 0,000 < 0,05. Then H1 is accepted. Variable X2 Asset Structure had a significant effect on Capital Structure with t count value is [-4,988] > t table [1,983] and sig 0.000 <0.05. Then H2 is accepted. From the F test, it was found that Business Risk and Asset Structure have a simultaneous effect on Capital Structure with f count [32,694] > f table 3,090 and a significance 0,000 < 0,05. Then H3 is accepted. From the coefficient of determination test the value of R square is 0.391. This means that the independent variables of Business Risk and Asset Structure affect the Capital Structure by 39.1% while the remaining 60.9% is influenced by other variables.